CHANGES IN REGIONAL BRAIN ACTIVATION RELATED TO DEPRESSIVE STATE: A 2‐YEAR LONGITUDINAL FUNCTIONAL MRI STUDY. Issue 1 (17th September 2015) - Opmeer, Esther M.; Kortekaas, Rudie; van Tol, Marie‐José; Renken, Remco J.; Demenescu, Liliana R.; Woudstra, Saskia; Ter Horst, Gert J.; van Buchem, Mark A.; van der Wee, Nic J. A.; Veltman, Dick J.; Aleman, André
Abstract : Background: Abnormal brain activations during processing of emotional facial expressions in depressed patients have been demonstrated. We investigated the natural course of brain activation in response to emotional faces in depression, indexed by functional magnetic resonance imaging (fMRI) scans preceding and following change in depressive state. We hypothesized a decrease in activation in the amygdala, anterior cingulate cortex (ACC), and insula with a decrease in depressive pathology. Methods: A 2‐year longitudinal fMRI study was conducted as part of the Netherlands Study of Depression and Anxiety. We included 32 healthy controls and 49 depressed patients. During the second scan, 27 patients were in remission (remitters), the other 22 were not (nonremitters). All participants viewed faces with emotional expressions during scanning. Results: Rostral ACC activation during processing of happy faces was predictive of a decrease in depressive state (PFWE = .003). In addition, remitters showed decreased activation of the insula over time (PFWE = .016), specifically during happy faces. Nonremitters displayed increased abnormalities in emotion recognition circuitry during the second scan compared to the first. No effect of selective serotonin reuptake inhibitor use was observed. Conclusions: Our results demonstrate that rostral ACC activation may predict changes in depressive state even at 2‐year outcome. The association between change in depressed state and change in insula activation provides further evidence for the role of the insula in a network maintaining emotional and motivational states.